A Study on the Emergence of SMEs & e- Commerce - Rajesh Chennattu Sasidharan Nair (International Journal of Supply Chain Management, 2022)
Abstract– The Covid-19 pandemic aggravated the effects of economic slowdown. With the closure of brick-and-mortar stores during lockdowns, restriction on physical movement of consumers and resulting rapid decline in sales businesses were force to turn digital and go online. It was this struggle for survival that forced the small and mid-sized enterprises (SMEs) to enter the international e-commerce arena. This article examines the scenario that propelled the SMEs into the global e-commerce, evaluates the present scenario and explores the way forward.